Letters from Joseph Bartholomew Skeffington concerning the imprisonment and hunger strike of Francis Sheehy-Skeffington, - Skeffington, J.B. (Joseph Bartholomew) 1850-1919 (1915)
Also includes two letters from Alfred Purser to Joseph Bartholomew concerning Francis Sheehy-Skeffington.